A systematic review of information systems and greenwashing detection models in corporate sustainability reporting (2024-2025) - Nara Pelita Sari Kaban; Sambas Ade Kesuma; Fahmi Natigor Nasution; Keulana Erwin (Trigin Publisher, 2026)
This study systematically reviewed recent developments in the use of information systems and digital technologies for detecting and reducing greenwashing in corporate sustainability reporting during the period of 2024–2025. Using a systematic literature review approach based on established guidelines, this study examined forty-five peer-reviewed journal articles published between January 2024 and September 2025. The findings showed that information systems had progressed from basic data management tools into integrated digital ecosystems that employed artificial intelligence, natural language processing, blockchain, and environmental, social, and governance analytics to identify misleading sustainability disclosures. The review revealed four major themes, namely digital transparency and data integrity, technology-driven detection and predictive analysis, governance and ethical structures, and sector-specific reporting practices. Although meaningful advancements had been achieved, several challenges persisted, particularly the absence of standardized digital verification models and limited accountability in algorithm-based assessments. This study contributed to theoretical and practical discussions by mapping how information-system-based models strengthened the credibility of sustainability reporting and by outlining future research directions to improve greenwashing detection mechanisms.